Pengembangan Model Kurikulum Grass Roots Berbasis Ahlisunah Waljamaah dalam Peningkatkan Mutu Pendidikan Raudlatul Athfal - Mumu Muzayyin Maq; Fitriyah Nurdianah; Ardi Dwi Susandi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aims to provide an overview of the grassroots curriculum development model based on ahlisunnah waljamaah (Aswaja) at the Raudlatul Athfal (RA) education level. A curriculum model for improving the quality of education in Raudlatul Athfal (RA) in Leuwimunding District, Majalengka Regency. The research method used in this research is the R&D model. The main product in this study is the grassroots curriculum model book. The product is then tested for validity, practicality, and effectiveness so that the curriculum model developed is proven to improve the quality of education for Raudlatul Athfal (RA). The results showed that the curriculum model was declared valid by experts so that it could be tested to determine its practicality and effectiveness. To determine the practicality and effectiveness of the curriculum model, field trials were conducted. After conducting field trials, the results show that the implementation of the curriculum model is in the high category so that the curriculum model meets the criteria for practicality. Then the students' responses were included in the positive criteria and the quality of education was included in the high category. It can be concluded that the curriculum model has met the criteria for effectiveness. Therefore, the grassroots model based on ahlisunnah waljamaah (Aswaja) has met all the criteria for the validity, practicality, and effectiveness of a curriculum model.